The Precautionary Principle as a Law Enforcement Instrument: Immigration Supervision of Foreign Workers at IMIP Morowali Airport to Maintain National Sovereignty - Lisda Syamsumardian; Adnan Hamid (Greenation International Journal of Law and Social Sciences, 2025)
This study examines the implementation of the precautionary principle as a law enforcement instrument in immigration supervision of foreign workers at the Indonesia Morowali Industrial Park (IMIP) Airport in Morowali to safeguard national sovereignty. The rapid development of the Morowali industrial area has resulted in high mobility of foreign workers, especially from China, thus requiring a strict and professional immigration supervision system. This normative juridical research uses a legislative and conceptual approach to analyze the legal basis, implementation mechanisms, and effectiveness of the precautionary principle in the context of immigration supervision. The results show that the precautionary principle has a strong legal basis in Law No. 6 of 2011 concerning Immigration as amended by Law No. 63 of 2024 and is implemented through a comprehensive immigration and employment document verification mechanism, an early detection system for potential violations, and integrated coordination between relevant agencies. The implementation of this principle is effective in preventing immigration law violations, protecting the interests of local workers, and maintaining national sovereignty. However, significant challenges remain, including the high volume of foreign worker arrivals, lIMIPed human resources, the complexity of employment documentation, and technical constraints in information technology infrastructure. The study recommends increasing the number of immigration officers, developing an integrated information system, developing more specific standard operating procedures, and strengthening inter-agency coordination through the formation of an integrated task force to optimize the effectiveness of immigration oversight in protecting national sovereignty.